(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
In this research, an exhaustive analysis is proposed that is framed in the latest conceptions of modern criminal law, from the fierce expansion of the functionalists and their -normativist- distinction. On the one hand, an attempt was made to examine Claus Roxin’s inference from his –teleological or moderate functionalism–, and then to contrast it with the position of Günter Jakobs and his recognized –standard or radical functionalism–. Likewise, it will be essential to promote discussion regarding the characteristics of the two positions that have solved contemporary criminal thought. The dogmatic spheres of systemic penal functionalism, from the philosophical and scientific context, were also part of the approach, to later culminate with a personal sketch that allowed to clear up questions about current penal functionalism. Therefore, it was approached from a descriptive method with the support of comparative legislation and fundamentally, from a direct interaction of modern thoughts on criminal law.